"Nobody Was a Librarian. We Were All Scientists": Exploring Three 20th-Century Women Scientists' Careers as Scientists of Information on the Cusp of Information Science. - Garwood, Deborah (Transactions of the American Philosophical Society, 2025)
The article explores the careers of three 20th-century women scientists—Claire Schultz, Madeline Berry Henderson, and Nathalie Dusoulier—who played pivotal roles in the development of Information Science. Through oral histories, the article highlights their contributions to scientific documentation and indexing, contrasting the evolution of scientific information practices in Europe and the United States. It emphasizes the significance of their work in establishing systems for organizing and retrieving scientific data, particularly in the context of the burgeoning field of chemical research. The author advocates for further recognition of these women's contributions to the foundations of Information Science and the importance of oral history in preserving their legacies.